A thermal slip temporary bonding adhesive based on hydrogen bond regulation and a preparation, bonding and debonding method thereof

CN122706284BActive Publication Date: 2026-10-23SHANGHAI UNIV OF ENG SCI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611199767.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-23
Estimated Expiration
2046-08-10

AI Technical Summary

Technical Problem

[0008]本发明克服了传统热滑移胶常温粘接强度与高温低应力剥离性能互斥的机理缺陷,实现温度可控可逆粘接;解决了胶层NMP、酸碱药液溶胀率高、耐化学性不足的问题,适配全制程湿法/干法加工;降低胶层厚度偏差TTV,抑制120~210℃制程区间高温蠕变,提升晶圆加工尺寸精度;实现180~210℃热滑移解键后基材零可见残胶,简化清洗工序,降低有机溶剂污染;提升树脂长期热循环稳定性,避免多次高温工序后胶层黄变、粘接性能衰减;提供完整配套制备、键合、解键工业化工艺,方案可稳定量产,适配8/12英寸大尺寸晶圆生产线

Benefits of technology

[0022]现有临时键合胶仅依靠树脂单一物理热软化实现剥离,粘接与剥离性能天然矛盾;本发明通过热可逆羟基-羰基氢键+同步温敏弹性体双重协同温控机制,从分子相互作用层面解决性能互斥问题。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of based on hydrogen bond regulation's thermal slip temporary bonding glue and its preparation, bonding and debonding method, bonding glue includes by weight parts: 56~68 nonpolar main solvent, 12~17 hydrogen bond type cosolvent, 40~46 ternary main resin, 2.8~4.2 silane coupling agent grafted nanosilica, 0.4~0.7 epoxy modified silicone resin, 0.2~0.5 hindered phenol antioxidant;Composite solvent and ternary resin construct hydroxyl-carbonyl thermal reversible hydrogen bond system, ternary resin is by hydrogenated styrene elastomer, cycloolefin copolymer, alicyclic acrylic resin compound, hydrogenated elastomer temperature-sensitive softening interval and hydrogen bond dissociation temperature are synchronous.The application simultaneously provides glue liquid preparation, wafer temporary bonding, thermal slip debonding complete process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of temporary bonding and packaging materials for semiconductor wafers, specifically relating to a thermally slipping temporary bonding adhesive based on thermally reversible hydrogen bond temperature control. Background Technology

[0002] In current advanced semiconductor packaging processes, wafer thickness is gradually decreasing to ultra-thin specifications of 20-100μm. Ultra-thin wafers have extremely low mechanical strength, making them prone to warping and breakage. Temporary bonding adhesives are necessary to bond and fix the functional wafer to the glass / silicon substrate, achieving damage-free and low-residue peeling after back-side processing. The industry mainstream uses heat-slip temporary bonding adhesives, relying on high-temperature softening of the resin to achieve peeling. However, existing products suffer from four irreconcilable core contradictions that hinder the improvement of high-end chip manufacturing yield:

[0003] There is a conflict between adhesive strength and thermal slip properties: conventional single thermoplastic resin adhesives exhibit strong adhesion at room temperature, but this results in excessively high resin softening temperatures, which can easily cause thermal deformation of the wafer. Conversely, lowering the softening temperature leads to insufficient adhesive strength at room temperature, causing bubbles and localized delamination during hot pressing and wet processing, resulting in scrap. Existing technologies rely solely on adjusting the resin ratio, which cannot simultaneously address the two opposing mechanical requirements at high and low temperatures.

[0004] Poor stability against chemical solutions: Wafer manufacturing processes involve strong corrosive solvents such as photolithography and development solutions, NMP stripping solutions, and acid and alkali cleaning solutions. Traditional hydrocarbon resin adhesive layers are prone to swelling and dissolution, losing their supporting function. Introducing polar tackifying resins to improve adhesion will further exacerbate solvent swelling, and the two cannot be addressed simultaneously.

[0005] Poor uniformity of adhesive layer thickness (high TTV) and severe high-temperature creep: lack of inorganic reinforcing filler or poor filler compatibility, large deviation in adhesive layer thickness after spin coating, poor thickness consistency after ultra-thin wafer thinning; creep flow of adhesive layer occurs during high-temperature process, wafer misalignment.

[0006] The amount of residual resin after debonding is large and the cleaning is difficult: After high-temperature peeling, the resin remains on the wafer surface, which requires long-term soaking and cleaning with highly toxic and high-boiling-point organic solvents, which increases the process cost, pollutes the environment, and can easily damage the structure of precision devices.

[0007] Existing improvement solutions only optimize single resins, single solvents, or single fillers, without constructing a temperature-responsive reversible molecular interaction system, and cannot solve all the above pain points at the mechanistic level. The industry urgently needs a temporary bonding adhesive with a new molecular interaction mechanism to achieve a breakthrough in integrated performance such as high viscosity at room temperature, easy peeling at high temperature, solvent resistance, low TTV, and no residue. Summary of the Invention

[0008] This invention overcomes the inherent mechanism defect of traditional hot-slip adhesives where room-temperature bonding strength and high-temperature, low-stress peeling performance are mutually exclusive, achieving temperature-controlled and reversible bonding. It solves the problems of high swelling rates and insufficient chemical resistance of the adhesive layer in NMP and acid / alkali solutions, making it suitable for all wet / dry processing processes. It reduces the thickness deviation (TTV) of the adhesive layer, suppresses high-temperature creep in the 120–210℃ process range, and improves wafer processing dimensional accuracy. It achieves zero visible adhesive residue on the substrate after hot-slip debonding at 180–210℃, simplifying the cleaning process and reducing organic solvent contamination. It improves the long-term thermal cycling stability of the resin, avoiding yellowing and adhesion degradation of the adhesive layer after multiple high-temperature processes. It provides a complete set of industrialized processes for preparation, bonding, and debonding, enabling stable mass production and adapting to 8 / 12-inch large-size wafer production lines.

[0009] To achieve the above objectives, the present invention provides the following technical solution: a hydrogen-bonded thermally sliding temporary bonding adhesive, the raw materials comprising, by weight, the following components: 56-68 parts of a nonpolar main solvent; 12-17 parts of a hydrogen-bonding co-solvent; 40-46 parts of a ternary host resin; 2.8-4.2 parts of a silane-grafted inorganic filler; 0.4-0.7 parts of an epoxy-modified silicone resin; and 0.2-0.5 parts of a hindered phenolic antioxidant; wherein the nonpolar main solvent and the hydrogen-bonding co-solvent are miscible to form a composite solvent system, and the composite solvent and the ternary host resin form a thermally reversible intermolecular hydrogen bond system; the hydrogen-bonding co-solvent carries hydroxyl groups as hydrogen bond donors, and the alicyclic acrylic resin side chain carbonyl groups of the ternary host resin act as hydrogen bond acceptors; the adhesive is prepared at room temperature to 180°C. In the ℃ range, hydrogen bonds associate extensively, enhancing adhesive strength. In the 180–210℃ range, hydrogen bonds dissociate upon heating, causing a sharp drop in interfacial forces. Combined with the temperature-sensitive softening of the resin, temperature-controlled thermal slip peeling is achieved. The ternary main resin is composed of hydrogenated styrene elastomer, cyclic olefin copolymer, and alicyclic acrylic resin. The styrene elastomer has a styrene unit content of 14%–50% by mass and exhibits temperature-sensitive characteristics of a sharp drop in modulus and softening of chain segments at high temperatures. Moreover, the temperature-sensitive response temperature is synchronously matched with the hydrogen bond dissociation temperature. The silane-grafted inorganic filler and epoxy-modified silicone resin synergistically construct a low-density physical / slightly cross-linked reinforcing network, improving the dimensional stability, high-temperature creep resistance, and solvent resistance of the adhesive film. Furthermore, the reinforcing network does not interfere with the reversible association and dissociation process of hydrogen bonds in the system.

[0010] Furthermore, the nonpolar main solvent is a cycloalkanes / fused-ring hydrocarbon containing only carbon and hydrogen elements, without polar functional groups, and with a boiling point ≥150℃ at normal pressure, selected from any one or more of decahydronaphthalene, tetrahydronaphthalene, and p-menthane; the nonpolar main solvent serves only as a resin dispersion medium and does not participate in hydrogen bond formation; the hydrogen-bonding co-solvent is a weakly polar alicyclic alcohol containing a single hydroxyl group and with a boiling point of 100-220℃ at normal pressure, selected from one or more of α-terpineol, β-terpineol, cyclohexanol, and cyclopentanol; the hydrogen-bonding co-solvent simultaneously functions as a resin solubilizer and a hydrogen bond donor, and is infinitely miscible with the nonpolar main solvent. The composite solvent is composed of a nonpolar main solvent that does not participate in hydrogen bonding and a hydrogen-bonding co-solvent that serves as a hydrogen bond donor, with only the hydrogen-bonding co-solvent forming a hydrogen bond network with the ternary resin.

[0011] Further, based on 100 parts by weight of the total ternary main resin: 50-98 parts of hydrogenated styrene elastomer; 1-49 parts of cyclic olefin copolymer; 1-49 parts of alicyclic acrylic resin; the hydrogenated styrene elastomer is a fully saturated ABA-type hydrogenated block copolymer, selected from one or more of hydrogenated polystyrene-poly(ethylene / propylene) block copolymer, hydrogenated styrene-ethylene-butene-styrene block copolymer, and hydrogenated styrene-isoprene-styrene triblock copolymer; it has no polar groups and does not participate in hydrogen bonding, relying on the physical entanglement of hard segments to provide room temperature rigidity and high temperature soft segment expansion to achieve modulus reduction; the cyclic olefin copolymer is an ethylene-norbornene fully saturated polyolefin with no polar functional groups, used to improve the solvent resistance and rigidity of the adhesive layer; the alicyclic acrylic resin is a thermoplastic random copolymer with a saturated main chain and ester carbonyl groups on the side chains, which is the only hydrogen bond acceptor in the system, forming reversible -OH…O=C- intermolecular hydrogen bonds with hydrogen-bonded cosolvent hydroxyl groups. In other words, ternary resin systems can form intermolecular hydrogen bonds with hydrogen-bonding cosolvents such as α-terpineol, β-terpineol, cyclohexanol, and cyclopentanol. The hydroxyl group (-OH) in the hydrogen-bonding cosolvent molecule acts as a hydrogen bond donor, and the ester carbonyl group (C=O) in the acrylic resin molecule acts as a hydrogen bond acceptor. The two interact to form stable hydroxyl-carbonyl hydrogen bonds (-OH…O=C-), which enhances the cohesion and compatibility of the resin system, while further reducing the swelling problem caused by the inhibitor solvent.

[0012] Furthermore, the hydrogenated styrene-based elastomer is a fully saturated ABA-type hydrogenated block copolymer. It has no polar functional groups and does not participate in the association reaction between hydrogen bond donors and acceptors. It relies on the physical entanglement of hard segments to provide rigidity at room temperature and the expansion of soft segments at high temperatures to achieve a sharp drop in modulus. Firstly, this resin possesses basic film-forming and system compatibility properties. Its molecule has a triblock structure with polystyrene (PS) hard segments at both ends and a saturated polyolefin soft segment in the middle. The fully hydrogenated process completely eliminates unsaturated double bonds in the molecular chain, preventing double bond oxidation crosslinking and resin hardening failure during high-temperature processing. The non-polar hydrocarbon skeleton is infinitely miscible with high-boiling-point cycloalkanes as a non-polar main solvent, making it the most abundant basic film-forming component in the ternary resin. It can form a continuous and complete film on its own, providing a continuous organic matrix for the entire bonded adhesive. This matrix supports the uniform dispersion of fillers, silicones, antioxidants, and other additives, preventing phase separation and particle agglomeration in the system. Within the room temperature processing range, the aforementioned molecular structure provides stable mechanical support. At both ends of the room temperature range (25–180°C), microphase separation occurs in the polystyrene hard segments, and a large number of hard segment micro-regions entangle with each other to form a physical cross-linking network. This provides the film with basic tensile strength and shear resistance without relying on covalent cross-linking. In medium and low temperature processes such as wafer hot pressing, it resists slippage and local debonding of the adhesive layer under external forces. Combined with the hydrogen bond network, it provides double protection against displacement, warping, and detachment during the ultrathin wafer processing. At the same time, the saturated hydrocarbon structure has no polar sites, so it does not compete for the hydroxyl donors that consume hydrogen bond-type cosolvents and does not interfere with the stable association of reversible hydrogen bonds between hydroxyl and carbonyl groups. When the system is heated to the debonding temperature range, the resin simultaneously exerts a temperature-sensitive dissociation effect, matching and synergistically with the hydrogen bond dissociation behavior. The styrene unit mass content is controlled at 14%–50%, and the dissociation temperature of the polystyrene hard segment micro-region is precisely controlled and locked at 180–210℃, which highly coincides with the temperature window for complete dissociation of hydroxyl-carbonyl hydrogen bonds. When the system is heated to the debonding temperature range, the hard segment microphase separation structure disintegrates simultaneously, the intermediate flexible soft segment fully expands, the elastic modulus of the adhesive layer decreases significantly, and the adhesive film exhibits lubricating, low-viscosity, and easy-slip properties. Hydrogen bond dissociation eliminates intermolecular interfacial adhesion, and the elastomer softening provides a low-resistance slip medium. The two work synergistically to significantly reduce the mechanical thrust required for wafer peeling, avoiding wafer chipping and breakage under stress. Based on the aforementioned three core properties of basic film formation, room temperature support, and high temperature sensitivity, the amount of this resin added can be adjusted to adapt to different wafer processing conditions. The formulation range of 50-98 parts can be adjusted as needed to adjust the proportion of elastomer. High addition (90-98 parts) significantly improves the toughness and low-temperature adhesion durability of the film, making it suitable for 12-inch large-size ultra-thin wafers and long-term multi-stage high-temperature cycle processes. Medium addition (50-80 parts) balances the adhesion strength and solvent resistance, making it universally suitable for 8-inch conventional packaging production lines. If the addition of this component is less than 50 parts, the continuous organic matrix of the system will break, the toughness of the film will be insufficient, and resin tearing and large-area residual adhesive defects will easily occur during high-temperature slippage.

[0013] Furthermore, the cyclic olefin copolymer is an ethylene-norbornene fully saturated polyolefin with no polar functional groups, used to improve the solvent resistance and rigidity of the adhesive layer; the main molecular chain is a saturated carbon-carbon single bond, and the side chains have a large number of rigid alicyclic structures, without polar active groups such as hydroxyl, carbonyl, and carboxyl groups, and does not participate in the reversible reaction of hydrogen bonding association and dissociation throughout the process, and is only used as an inert reinforcing resin compound.

[0014] First, this resin provides chemical barrier properties. Its fully saturated hydrocarbon alicyclic structure exhibits extremely high chemical inertness, with no polar sites easily eroded by solvents. This allows it to form a dense hydrophobic barrier network within the adhesive layer, preventing strong corrosive solutions such as NMP stripping fluid and acid / alkali cleaning solutions from penetrating into the film and significantly reducing solvent swelling. Without this component, the large free volume within the hydrogenated elastomer matrix makes it highly susceptible to organic solvent penetration and swelling, leading to blistering of the adhesive layer and localized wafer detachment during hot pressing. Furthermore, the resin's rigid alicyclic structure imparts high-temperature creep resistance and dimensional stability to the adhesive layer. The rigid cyclic side chains possess extremely high steric hindrance, constraining the free flow of the flexible segments of the hydrogenated styrene elastomer at high temperatures and inhibiting creep flow during medium-high temperature processes such as hot pressing and etching at 120–150°C. This reduces lateral wafer offset under high-temperature loads and improves the overall thickness uniformity (TTV) after back-side thinning of ultra-thin wafers. It also forms an organic-inorganic dual creep-resistant framework with silane-grafted inorganic fillers. Simultaneously, the resin can optimize the rigidity and overall thermal stability of the film. The high glass transition temperature (Tg) and alicyclic structure enhance the hardness of the film at room temperature, reduce the deformation of the adhesive layer under external pressure, and avoid void defects caused by uneven local pressure after wafer bonding. The molecular 5% thermal weight loss temperature exceeds 300℃, which is higher than the temperature of all processes in the system. It does not decompose or volatilize after long-term heat treatment at 220℃. Based on the above multiple fundamental properties, the formulation can be adapted to different processes by adjusting the amount of this resin added. The addition range of 1 to 49 parts can flexibly adapt to different process requirements. The high addition amount (30 to 49 parts) enhances solvent resistance and creep resistance, and is suitable for long-term wet cleaning and NMP stripping processes. The low addition amount (1 to 10 parts) reduces the hardness of the film and improves the smoothness of thermal sliding, and is suitable for low-temperature debonding conditions of ultra-thin and fragile compound wafers. The addition amount exceeding 49 parts will destroy the continuous matrix of hydrogenated elastomer, making the film brittle and prone to resin breakage during stripping, leaving a large amount of residual resin.

[0015] Furthermore, the alicyclic acrylic resin is a thermoplastic copolymer with a saturated main chain and ester carbonyl groups on the side chains. It is the only hydrogen bond acceptor in the system and forms reversible -OH…O=C- intermolecular hydrogen bonds with the hydrogen-bonded cosolvent hydroxyl groups. The saturated carbon chain of the main chain, combined with the alicyclic side groups, does not decompose or carbonize during high-temperature processing, ensuring the stability of the hydrogen bond network throughout the entire process temperature range.

[0016] First, this resin plays a core role in constructing a thermally reversible hydrogen bond network. The resin side chains have a large number of uniformly distributed ester carbonyl groups (C=O), which are the only hydrogen bond acceptors in the system that can pair with the hydroxyl groups (-OH) of hydrogen-bonded cosolvents such as α-terpineol and cyclohexanol. From room temperature to 180°C, a large number of hydroxyl-carbonyl molecules uniformly associate hydrogen bonds, forming a dynamic molecular force network that runs through the entire film. This significantly improves the compatibility between the three phases of the ternary resin, solves the problem of interfacial incompatibility between nonpolar hydrogenated elastomers, cyclic olefin copolymers and weakly polar alcohol cosolvents, and ensures that the adhesive solution remains clear and transparent, does not separate, and does not precipitate during long-term storage. Based on the formed continuous hydrogen bond network, the resin can further enhance the interfacial adhesion strength of the adhesive layer at room temperature. The hydrogen bond association simultaneously strengthens the interfacial adhesion between the adhesive layer and silicon wafers and glass substrates, compensating for the weak interfacial forces between pure hydrocarbon resins and inorganic substrates. Hydrogen bonds are reversible weak intermolecular interactions, which can be completely dissociated at temperatures above 180°C, unlike covalently cross-linked resins which permanently lock the adhesive interface and do not hinder high-temperature thermal slip separation. At the same time, the hydrogen bond network can also play an auxiliary role in reducing solvent swelling. The hydrogen bond network tightens the spacing between resin molecular chains, reduces the free volume inside the adhesive film, and forms a molecular-level dense barrier, further blocking the penetration of polar organic solvents and synergistically reducing the swelling rate of the adhesive layer with cyclic olefin copolymers. Based on this, the resin's inherent structural characteristics endow it with dual functions of heat resistance and adjustable formulation. The alicyclic saturated side groups give the resin excellent thermal stability, preventing the decomposition and generation of small molecule volatiles during high-temperature processes, thus avoiding foaming of the adhesive layer and wafer contamination. The hydrogen bond density can be adjusted as needed by adding 1 to 49 parts. High addition (30 to 49 parts) significantly increases the number of hydrogen bonds in the system, and the bonding strength reaches its peak at room temperature, making it suitable for ultra-thin wafer thinning processes with extremely high requirements for bonding strength. Low addition (1 to 10 parts) has a moderate hydrogen bond density, balancing bonding strength and high-temperature slippage smoothness, making it suitable for high-temperature coating production lines with multiple cycles. Adding more than 49 parts will significantly increase the overall polarity of the system, weaken the solvent resistance of hydrogenated elastomers and cyclic olefin copolymers, and cause slight swelling when immersed in NMP. In addition, this resin exhibits no negative interference during system compounding and is well-suited to the overall formulation design: the resin molecules contain only ester carbonyl hydrogen bond active sites, lacking competing polar groups such as free hydroxyl and carboxyl groups. It does not compete for hydrogen bond donors, nor does it undergo side reactions with hindered phenolic antioxidants or epoxy-modified silicone resins. Throughout the process, it does not disrupt the low-density, slightly cross-linked network and thermally stable system, ensuring that the functions of each component in the formulation do not interfere with each other and achieve synergistic effects. Furthermore, the silane-grafted inorganic filler is selected from one or more of the following: silane coupling agent-grafted nano-silica, siloxane-grafted nano-alumina, silane-grafted talc, and silane-grafted montmorillonite. The native silanol groups on the filler surface undergo dehydration condensation with the silane coupling agent to form a ≡Si-O-Si≡ covalent graft layer, improving the interfacial compatibility between the inorganic filler and the organic resin, reducing the thickness deviation (TTV) of the adhesive layer, and without disrupting the dynamic equilibrium of hydrogen bonds.

[0017] Furthermore, the epoxy-modified silicone resin backbone consists of Si-O-Si inorganic covalent bonds with side-linked epoxy active groups. Only a low-density, mildly cross-linked network is formed within the system, which only improves high-temperature creep resistance without restricting resin chain movement or blocking the reversible association and dissociation of hydroxyl-carbonyl hydrogen bonds. At low temperatures, the epoxy groups undergo ring-opening reactions to form a low-density, irreversible, mildly covalently cross-linked network. The cross-linking density is extremely low, which does not restrict resin chain movement or block the reversible association and dissociation of hydroxyl-carbonyl hydrogen bonds, only improving high-temperature creep resistance. At low temperatures, the epoxy-modified silicone resin forms a low-density, mildly irreversible covalently cross-linked network with very few cross-linking points, preventing the locking of the soft segments of the hydrogenated elastomer. Above 180°C, the cross-linked network has no rigid constraints, allowing resin chains to freely extend and hydrogen bonds to dissociate synchronously, without affecting thermal slip separation.

[0018] Furthermore, the hindered phenolic antioxidant is selected from one or more of antioxidant 1135, antioxidant 1076, and antioxidant 405; the molecule contains only hindered phenolic active sites and has no strong polar groups, which can inhibit the high-temperature oxidative thermal degradation of the resin, does not undergo side reactions with hydrogen bond donors / acceptors, and stably maintains the integrity of the hydrogen bond system under long-term thermal cycling.

[0019] Furthermore, the preferred weight parts and raw materials for each component are as follows: the non-polar main solvent is tetrahydronaphthalene, 62-68 parts; the hydrogen-bonding co-solvent is α-terpineol, 12-17 parts; the total ternary main resin is 41-42 parts, which is a compound of SEBS hydrogenated styrene-ethylene-butene block copolymer, TOPAS cyclic olefin copolymer, and Dianal alicyclic acrylic resin; silane coupling agent grafted with nano-silica is 3.0-3.2 parts; epoxy modified organosilicon resin is 0.4-0.5 parts; and antioxidant 1076 is 0.2-0.3 parts.

[0020] This invention integrates a ternary resin compound system with the thermally reversible intermolecular hydrogen bond temperature control mechanism to solve problems such as the contradiction between bonding strength and thermal slip performance, large thickness deviation (TTV) of adhesive layer, and a lot of debonding residue in existing products. It achieves a comprehensive effect of strong bonding at room temperature, non-destructive thermal slip at high temperature, low swelling, high cleanliness, and high dimensional accuracy, and is fully adaptable to the entire precision process of ultra-thin semiconductor wafer manufacturing.

[0021] The present invention has the following beneficial effects:

[0022] Existing temporary bonding adhesives rely solely on the physical thermal softening of the resin to achieve peeling, resulting in an inherent contradiction between bonding and peeling properties. This invention addresses the performance incompatibility issue at the molecular interaction level through a dual synergistic temperature control mechanism of thermally reversible hydroxyl-carbonyl hydrogen bonds and synchronously temperature-sensitive elastomers.

[0023] The stability of the adhesive solution in this invention: In the example, the transmittance was 92%–94%, and no stratification or resin precipitation occurred after 3 months of storage at room temperature; in Comparative Example 1, after replacing the hydrogen bonding co-solvent, the transmittance was only 45%, and the system directly failed; Adhesive layer dimensional accuracy: TTV controlled ≤1.9μm, far below the industry standard of 3–5μm; after removing epoxy silicone, the TTV increased to 3.8μm; Solvent resistance: NMP swelling rate ≤2.6%, with a qualified threshold of 3.0%, and can withstand long-term immersion in photolithography and stripping solutions; High-temperature thermal stability. No yellowing or foaming after prolonged heating at 220℃ (Heat stability level I); Yellowing and aging after thermal cycling of samples without antioxidants (level II); Thermal sliding effect: Smooth sliding without jamming at 180~210℃ (level 1); Sliding jamming and incomplete peeling of unhydrogenated SBS (level 3); Residual adhesive control: No visible adhesive residue after debonding (level A), no need for prolonged cleaning with highly toxic organic solvents; Room temperature bonding durability: No debonding after 7 days of long-term placement; Sliding and debonding of samples lacking acrylic acid hydrogen bond acceptors after 3 days.

[0024] The preparation process of this invention is mild, with a maximum temperature of 60°C throughout. It involves no high-temperature polymerization and no byproducts, resulting in high raw material utilization and low mass production costs. The spin coating, pre-baking, hot pressing, and debonding equipment are all mature and commonly used semiconductor equipment, requiring no additional special equipment and simplifying production line modifications. The debonding temperature is 180–210°C, lower than the debonding temperature of over 230°C for many high-temperature hot-slip adhesives, significantly reducing the risk of thermal warpage and thermal damage to ultra-thin wafers. The cleaning process is simplified, requiring only a short wipe with ordinary alcohol to completely remove trace amounts of loose adhesive, reducing hazardous waste treatment costs and improving environmental friendliness.

[0025] This invention fully covers the entire process of 8 / 12-inch ultrathin wafer thinning, etching, PVD / CVD coating, and wet cleaning; the cleanliness of the adhesive solution after 0.22μm filtration meets the requirements of advanced packaging cleanrooms; all formula components are semiconductor electronic-grade commercial raw materials with stable supply and large-scale mass production capability. Detailed Implementation

[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0027] A temporary thermally slipped adhesive based on hydrogen bond regulation is prepared by means of the following components by weight: 56-68 parts of nonpolar main solvent; 12-17 parts of hydrogen-bonded co-solvent; 40-46 parts of ternary main resin; 2.8-4.2 parts of silane-grafted inorganic filler; 0.4-0.7 parts of epoxy-modified silicone resin; and 0.2-0.5 parts of hindered phenolic antioxidant. This invention solves the industry pain points of traditional temporary adhesives, such as insufficient adhesion at room temperature, difficulty in high-temperature peeling, large dimensional deviation of adhesive layer, poor solvent resistance, high-temperature creep, and long-term thermal aging, by constructing a thermally reversible hydrogen bond temperature control system and an inorganic-organic synergistic reinforcing skeleton. It achieves integrated performance of high adhesion at room temperature, non-destructive thermal slip at 180-210℃, low TTV, no residue, chemical resistance, and thermal stability.

[0028] In this invention, a nonpolar main solvent and a hydrogen-bonded co-solvent are miscible to form a composite solvent system. The composite solvent and the ternary host resin form a thermally reversible intermolecular hydrogen bond system. The hydrogen-bonded co-solvent carries hydroxyl groups as hydrogen bond donors, and the alicyclic acrylic resin side chain carbonyl groups of the ternary host resin act as hydrogen bond acceptors. In the range of room temperature to 180°C, a large number of hydrogen bonds associate to enhance the adhesive strength. In the range of 180-210°C, hydrogen bonds dissociate upon heating, and the interfacial forces drop sharply. Combined with the temperature-sensitive softening of the resin, temperature-controlled thermal slip-off is achieved. This invention constructs a temperature-reversible hydroxyl-carbonyl dynamic hydrogen bond mechanism, which solves the core contradiction between the room temperature adhesive strength and high temperature peel performance of traditional adhesives at the molecular level. In the low temperature range, the dense association of hydrogen bonds greatly enhances the cohesive force and interfacial adhesion of the adhesive layer, ensuring that the wafer does not debond throughout the entire wafer processing. In the high temperature range, the hydrogen bond breakage directly reduces the interfacial molecular forces. Simultaneously, the resin softening weakens the adhesive force twice. Only a slight external force is required for slip-off separation, without tearing stress, and the ultra-thin wafer is not easily broken.

[0029] The ternary resin is composed of a hydrogenated styrene elastomer, a cyclic olefin copolymer, and an alicyclic acrylic resin. The hydrogenated styrene elastomer has a styrene unit content of 14%–50% and exhibits thermosensitive characteristics of rapid modulus drop and segment softening at high temperatures. Furthermore, this thermosensitive response temperature is synchronously matched with the hydrogen bond dissociation temperature. The microphase separation and dissociation temperature of the styrene hard segments is controlled within 180–210°C depending on the styrene content of 14%–50%, coinciding with the thermodynamic temperature window for hydroxyl-carbonyl hydrogen bond dissociation, thus achieving a dual-effect superposition. The ternary resin of this invention forms a functionally complementary matrix. The hydrogenated styrene elastomer provides thermosensitive softening characteristics synchronous with the hydrogen bond dissociation temperature, allowing hydrogen bond dissociation and resin modulus decrease to occur simultaneously, amplifying the high-temperature, low-adhesion effect. The styrene content range of 14%–50% ensures sufficient rigidity for physical entanglement of hard segments at room temperature and full expansion of soft segments at high temperatures, avoiding excessive adhesion or slippage / jamming problems associated with single resins.

[0030] Silane-grafted inorganic fillers and epoxy-modified silicone resin synergistically construct a low-density physical / mildly cross-linked reinforcing network, improving the dimensional stability, high-temperature creep resistance, and solvent resistance of the adhesive film. Furthermore, the reinforcing network does not interfere with the reversible association and dissociation of hydrogen bonds in the system. This invention's synergistic reinforcement of inorganic fillers and silicone resin, without compromising the reversible temperature control function of hydrogen bonds, dually constrains the high-temperature flow of resin molecular chains, suppressing creep flow of the adhesive layer during processes at 120–210°C, and reducing the risk of wafer misalignment. Simultaneously, it improves the film's density, reduces the penetration and swelling of solvents such as photolithography solutions and NMP, significantly reduces the thickness deviation (TTV) of the adhesive layer, and improves the dimensional accuracy of ultra-thin wafer processing.

[0031] In a preferred embodiment of the present invention, the nonpolar main solvent is a cycloalkanes / fused-ring hydrocarbons containing only hydrocarbon elements, nonpolar functional groups, and a boiling point ≥150℃ at normal pressure, selected from any one or more of decahydronaphthalene, tetrahydronaphthalene, and p-menthane; the nonpolar main solvent serves only as a resin dispersion medium and does not participate in hydrogen bond formation; the nonpolar pure hydrocarbon structure can completely dissolve two types of nonpolar resins, namely hydrogenated styrene elastomers and cycloolefin copolymers, and the adhesive solution does not separate or precipitate during long-term storage; the high boiling point characteristic reduces the rapid evaporation of solvents during pre-drying and hot-pressing stages, avoiding the formation of bubbles and pinholes in the adhesive layer; the nonpolar groups do not compete for hydrogen bond donors and acceptors, and do not disrupt the reversible hydrogen bond system of hydroxyl-carbonyl groups.

[0032] The hydrogen-bonding cosolvent is a weakly polar alicyclic alcohol containing a single hydroxyl group and a boiling point of 100–220 °C at normal pressure, selected from one or more of α-terpineol, β-terpineol, cyclohexanol, and cyclopentanol. The hydrogen-bonding cosolvent simultaneously functions as a resin solubilizer and a hydrogen bond donor, and is infinitely miscible with the nonpolar main solvent. This invention's single-hydroxyl weakly polar alcohol is not only completely miscible with the nonpolar main solvent but also provides stable hydrogen bond donor sites, building a hydrogen bond network that penetrates the adhesive layer. Simultaneously, it improves the compatibility between nonpolar hydrocarbon resins and polar acrylic resins, reducing the degree of swelling of the adhesive layer by organic solvents. The boiling point range matches the process temperature, preventing significant volatilization and loss during the pre-baking stage, ensuring stable hydrogen bonding throughout the process.

[0033] In a preferred embodiment of the present invention, based on 100 parts by weight of the total ternary main resin: 50-98 parts of hydrogenated styrene elastomer; 1-49 parts of cyclic olefin copolymer; and 1-49 parts of alicyclic acrylic resin. The three-stage resin ratio range of the present invention achieves adjustable performance. The high elastomer ratio is suitable for high-strength bonding conditions of large-size ultra-thin wafers; the high cyclic olefin ratio enhances solvent resistance; and the high acrylic resin ratio improves room temperature bonding strength, adapting to the needs of different packaging production lines. Reversible hydrogen bonds and temperature-sensitive slip matrix can be stably formed within the ratio range.

[0034] In a preferred embodiment of the present invention, the hydrogenated styrene-based elastomer is a fully saturated ABA-type hydrogenated block copolymer, selected from one or more of hydrogenated polystyrene-poly(ethylene / propylene) block copolymer, hydrogenated styrene-ethylene-butene-styrene block copolymer, and hydrogenated styrene-isoprene-styrene triblock copolymer. Its non-polar groups do not participate in hydrogen bonding; it relies on the physical entanglement of hard segments to provide room-temperature rigidity and the expansion of soft segments at high temperatures to achieve a decrease in modulus. The fully hydrogenated structure eliminates unsaturated double bonds, avoiding oxidative crosslinking and hardening during high-temperature processing. The ABA triblock structure relies on the separation of polystyrene hard segment microphases at room temperature to form physical crosslinks, giving the adhesive layer basic rigidity. At high temperatures, the soft segment expansion results in a sharp decrease in modulus, providing a low-modulus matrix required for thermal slip, and the non-polar groups in the molecule do not interfere with hydrogen bond formation and dissociation.

[0035] In a preferred embodiment of the present invention, the cyclic olefin copolymer is an ethylene-norbornene fully saturated polyolefin with no polar functional groups, which is used to improve the solvent resistance and rigidity of the adhesive layer; the saturated alicyclic hydrocarbon structure has strong chemical inertness and can resist the erosion of NMP, acid and alkali cleaning solutions, and photolithography stripping solutions, thereby reducing the swelling rate of the adhesive layer; the rigid cyclic structure improves the overall hardness of the adhesive film, further inhibits high-temperature creep, helps reduce TTV, does not participate in hydrogen bonding reactions, and does not change the temperature-controlled bonding characteristics.

[0036] In a preferred embodiment of the present invention, an alicyclic acrylic resin is a thermoplastic random copolymer with a saturated main chain and ester carbonyl groups on the side chains. It serves as the sole hydrogen bond acceptor in the system, forming reversible -OH…O=C- intermolecular hydrogen bonds with the hydrogen-bonding cosolvent hydroxyl groups. The abundant ester carbonyl groups on the side chains provide sufficient binding sites for hydrogen bonds, making them a core component in constructing the thermally reversible hydrogen bond network; their absence would significantly reduce the adhesive strength at room temperature. The alicyclic structure endows the resin with excellent heat resistance, with a 5% thermogravimetric temperature of ≥280℃, ensuring that it does not decompose or carbonize during high-temperature processes and guaranteeing the stability of the hydrogen bond system within the processing temperature range.

[0037] In a preferred embodiment of the present invention, the silane-grafted inorganic filler is selected from one or more of the following: silane coupling agent-grafted nano-silica, siloxane-grafted nano-alumina, silane-grafted talc, and silane-grafted montmorillonite. The native silanol groups on the filler surface undergo dehydration condensation with the silane coupling agent to form a ≡Si-O-Si≡ covalent graft layer, improving the interfacial compatibility between the inorganic filler and the organic resin, reducing the thickness deviation (TTV) of the adhesive layer, and without disrupting the dynamic equilibrium of hydrogen bonds. The present invention eliminates interfacial defects between the inorganic filler and the organic resin through silane covalent grafting modification. The filler is free of agglomeration and voids, resulting in a uniform adhesive layer thickness after spin coating, with TTV controllable within 2 μm. The inorganic rigid particles restrict the flow of resin molecular chains, improving high-temperature creep resistance. The filler provides only physical reinforcement, has no polar active groups, does not consume hydrogen bond donors or acceptors, and does not affect the reversible hydrogen bond association-dissociation cycle.

[0038] In a preferred embodiment of the present invention, the epoxy-modified silicone resin backbone is composed of Si-O-Si inorganic covalent bonds with epoxy active groups branched onto the side links. Only a low-density, mildly cross-linked network is formed within the system, which only improves high-temperature creep resistance without restricting resin chain movement or blocking the reversible association and dissociation of hydroxyl-carbonyl hydrogen bonds. The present invention enhances overall heat resistance stability through the high bond energy Si-O-Si backbone; at low temperatures, epoxy groups slowly form low-density, mildly cross-linked structures, helping to suppress high-temperature adhesive layer flow; the extremely low cross-linking density does not lock the movement of the soft segments of the hydrogenated elastomer, allowing hydrogen bonds to freely associate and dissociate without weakening the thermal slip-peeling effect.

[0039] In a preferred embodiment of the present invention, the hindered phenolic antioxidant is selected from one or more of antioxidants 1135, 1076, and 405; the molecule contains only hindered phenolic active sites and no strongly polar groups, which can inhibit the high-temperature oxidative thermal degradation of the resin, and does not undergo side reactions with hydrogen bond donors / acceptors, thus maintaining the integrity of the hydrogen bond system under long-term thermal cycling. The present invention captures oxidative free radicals generated during high-temperature processing, preventing thermal aging, yellowing, and degradation of adhesive properties of ternary resins; the molecule has no free hydroxyl, carbonyl, or other polar groups, and will not compete with the hydrogen bond donors and acceptors of the system for binding, maintaining the stability of the hydrogen bond network structure after long-term and repeated thermal cycling, thus extending the service life of the adhesive and the applicable window of the wafer fabrication process.

[0040] In a preferred embodiment of the present invention, the preferred weight parts and raw materials of each component are as follows: the nonpolar main solvent is tetrahydronaphthalene, 62-68 parts; the hydrogen-bonding co-solvent is α-terpineol, 12-17 parts; the total ternary main resin is 41-42 parts, which is a compound of SEBS hydrogenated styrene-ethylene-butene block copolymer, TOPAS cyclic olefin copolymer, and Dianal alicyclic acrylic resin; silane coupling agent grafted with nano-silica is 3.0-3.2 parts; epoxy modified organosilicon resin is 0.4-0.5 parts; and antioxidant is 1076, 0.2-0.3 parts. This optimized formula boasts the best overall performance, with a light transmittance of over 92%, stable storage without delamination, TTV ≤ 1.5μm, NMP swelling rate below 2.2%, no yellowing or foaming at 220℃, smooth thermal sliding without jamming at 200℃, no visible adhesive residue on the substrate after debonding, and strong adhesion at room temperature for 7 days, perfectly suited for the entire mass production process of 8 / 12-inch ultra-thin wafers.

[0041] This invention relies on the synergistic effect of a stable covalent backbone and thermally reversible intermolecular hydrogen bonds. The chemical structures, bonding forms, and working mechanisms of each component are as follows:

[0042] Hydrogenated styrene-based block copolymers: These copolymers exhibit a typical ABA-type fully saturated triblock structure, simplified as PS-EB-PS. Both ends consist of hard polystyrene segments with repeating unit structures of -[-CH2-CH(C6H5)-]m-, while the middle segment is an ethylene-butene soft segment formed from hydrogenated polybutadiene with a chain segment structure of -[-CH2-CH2-]x-[-CH2-CH(CH3)-]y-. After hydrogenation, the unsaturated double bonds in the molecular chain are fully saturated, leaving only carbon-carbon single bonds and carbon-hydrogen bonds. There are no polar functional groups, and the copolymer itself does not participate in hydrogen bonding. At room temperature, the hard polystyrene segments undergo microphase separation and physical entanglement, forming a stable physical cross-linked network that imparts rigidity and adhesive strength to the adhesive layer. When the temperature rises to the required processing range, the physical cross-linking points of the hard segments gradually dissociate, the soft segments in the middle fully expand, and the modulus of the adhesive layer decreases significantly, thus achieving a thermal slip effect.

[0043] Represented by styrene-ethylene-butene-styrene block copolymers (SEBS), these copolymers consist of hard polystyrene (PS) segments at both ends and soft ethylene-butene (EB) segments formed by hydrogenated polybutadiene in the middle. After hydrogenation, the unsaturated double bonds in the molecular chain are completely saturated, containing only carbon-carbon single bonds and carbon-hydrogen bonds. Lacking polar functional groups, they do not participate in hydrogen bond formation and primarily serve as the thermal slip physical framework of the system.

[0044] SEBS general structure:

[0045] Ph-[-CH2-CH(Ph)-]m-[-CH2-CH2-]x-[-CH2-CH(CH3)-]y-[-CH2-CH(Ph)-]n-Ph;

[0046] In the formula: Ph represents a benzene ring; the segments Ph-[-CH2-CH(Ph)-]m- and -[-CH2-CH(Ph)-]n-Ph are the polystyrene (PS) hard segments at both ends; the segments [-CH2-CH2-]x-[-CH2-CH(CH3)-]y- are the ethylene-butene (EB) soft segments in the middle.

[0047] At room temperature, the polystyrene hard segments at both ends form a stable physical cross-linked network through physical entanglement and microphase separation, endowing the adhesive layer with rigidity and initial bonding strength. When the temperature rises to the required range, the PS hard segments dissociate in micro-regions, the flexible EB segments in the middle fully extend, and the modulus of the adhesive layer decreases significantly, achieving a thermal slip effect. Its temperature response rhythm can be synchronized with the dissociation process of hydrogen bonds within the system, synergistically completing the reversible process of high-strength bonding at room temperature and low-stress peeling at high temperature.

[0048] Cyclic olefin copolymers: Fully saturated cyclic polyolefins obtained by copolymerizing ethylene and norbornene, with a pure hydrocarbon structure, no polar functional groups, and do not participate in hydrogen bonding.

[0049] The cyclic olefin resin used in this invention is an ethylene-norbornene cyclic olefin copolymer, a nonpolar alicyclic thermoplastic resin that mainly serves as a reinforcing phase and solvent-resistant reinforcing phase in ternary resin compounding systems. The molecular backbone is composed of saturated carbon-carbon bonds, and the side chains have rigid alicyclic structures, lacking polar functional groups and not participating in hydrogen bond formation. The typical molecular structure is a random copolymer of ethylene and norbornene (or tetracyclododecene and other polycyclic olefins), and its general structural formula can be represented as: -[-CH2-CH2-]a-[-CH(CH3)-CH2-]b-;

[0050] Alicyclic acrylic random copolymers (hydrogen bond acceptors): As a weakly polar resin, the main molecular chain is a saturated carbon chain, and its side chains contain a large number of ester carbonyl groups (C=O), which are the main hydrogen bond acceptors in the system; at the same time, the alicyclic structure endows the resin with excellent heat resistance, with a 5% thermal weight loss temperature ≥280℃, which can maintain the stability of the adhesive layer structure in high-temperature processes.

[0051] In the ternary polymer resin, the alicyclic acrylic resin acts as the main hydrogen bond acceptor. Its polymer backbone repeating unit structure is -[-CH2-CH(COOR)-]p-, with side chains containing ester functional groups -C(=O)-OR, where the ester carbonyl group is the core hydrogen bond interaction site. This resin also possesses excellent heat resistance, ensuring structural stability of the adhesive layer during high-temperature processes. The hydrogen-bonding cosolvent molecule carries an alcohol hydroxyl group R-OH, which acts as a hydrogen bond donor, forming a hydroxyl-carbonyl intermolecular hydrogen bond with the ester carbonyl group of the acrylic resin. The interaction mode is R-OH…O=C(-OR')-R'', where the dashed line represents a weak intermolecular interaction.

[0052] Hydrogen-bonded cosolvents: Represented by α-terpineol, these molecules contain a single hydroxyl group and serve as hydrogen bond donors in this system, playing a dual role in both solubilization and hydrogen bonding in the formulation. The core functional group is the hydroxyl group (-OH), which is the key site for providing hydrogen bonds. Structural characteristics: An alicyclic monoterpene skeleton containing only one hydroxyl group, with the rest being saturated carbon chains. It exhibits moderate polarity and excellent miscibility with hydrocarbon main solvents. The hydroxyl group (-OH) in the molecule acts as a hydrogen bond donor, forming a stable hydroxyl-carbonyl hydrogen bond with the ester carbonyl group (C=O) of the alicyclic acrylic resin side chain: R-OH…O=C(-OR')-R''. At room temperature, this significantly enhances the compatibility between resin components, improves the overall cohesiveness of the adhesive layer, and reduces the risk of swelling.

[0053] Thermally reversible intermolecular hydrogen bonds: This invention achieves temperature-controlled adjustment of the cohesive force and adhesive strength of the adhesive layer by constructing thermally reversible intermolecular hydrogen bonds between the ester carbonyl group of the resin side chain and the hydroxyl group of the cosolvent. No covalent bonds break throughout the process, and the process is reversible. Hydrogen bonds are weak intermolecular interactions that can reversibly associate and dissociate with temperature, without any covalent bond breakage.

[0054] Resin-C=O…HO-R⇆Resin-C=O+HO-R, where: Resin-C=O is the ester carbonyl group (hydrogen bond acceptor) of the alicyclic acrylic resin side chain; HO-R is the hydroxyl group (hydrogen bond donor) of hydrogen-bonded cosolvents such as α-terpineol; the dashed line represents intermolecular hydrogen bond interactions.

[0055] In the range of room temperature to 180℃: hydrogen bonds associate, the cohesive force of the adhesive layer and the interfacial adhesion are enhanced, and the wafer is firmly bonded; in the high temperature range of 180~210℃: hydrogen bonds dissociate when heated, the interfacial force is greatly reduced, and with the softening of the resin, non-destructive thermal sliding peeling is achieved.

[0056] Silane-modified inorganic filler: This invention uses silane-modified silica as an inorganic filler. The silanol groups on the surface of the native silica undergo a dehydration condensation reaction with the silane coupling agent to form a stable siloxane graft layer on the filler surface, constructing a rigid framework for the adhesive layer without interfering with the hydrogen bonding in the system.

[0057] Bonding reaction formula: ≡Si-OH + HO-Si≡ ≡Si-O-Si≡+H₂O, ≡Si-OH are silanol groups on the surface of silica; HO-Si≡ are hydrolyzable siloxane groups of silane coupling agents; the ≡Si-O-Si≡ covalent bond structure formed after the reaction significantly improves the interfacial compatibility between the filler and the organic resin, while giving the adhesive layer higher rigidity, dimensional stability and solvent resistance.

[0058] The present invention uses epoxy-modified silicone resin as a temperature-resistant reinforcing phase. Its main molecular chain consists of high-bond-energy siloxane inorganic covalent bonds, and its side chains have epoxy functional groups. It can form a low-density, slightly cross-linked network inside the adhesive layer, which only improves the high-temperature creep resistance and does not restrict the movement of resin chain segments and the thermally reversible dissociation process of hydrogen bonds.

[0059] The general structure of the main chain is: -[Si(R)2-O]n-, where R can be methyl, phenyl or an organic substituent containing an epoxy group; this resin combines the high temperature resistance of inorganic siloxanes with the reactivity of epoxy groups, improving the high temperature stability of the adhesive layer without affecting the thermal slip and reversible hydrogen bonding characteristics of the system.

[0060] This invention also provides a method for preparing a hydrogen-bonded thermally slipped temporary adhesive, comprising the following steps performed sequentially:

[0061] Step 1: Preparation of composite hydrogen-bonding solvent: Mix the nonpolar main solvent with the hydrogen-bonding co-solvent, and stir at a constant temperature of 25-35℃ for 10-15 minutes to obtain a uniform and transparent composite solvent. Low-temperature constant-temperature stirring avoids the high-temperature volatilization of the hydrogen-bonding co-solvent, ensures that the hydroxyl hydrogen bond donors are uniformly dispersed in the solvent, and builds a uniform hydrogen bond medium in advance to prevent uneven local hydrogen bond concentration and local viscosity differences in the adhesive solution during subsequent resin dissolution.

[0062] Step 2, dissolving the base resin solution: Add the ternary main resin to the composite solvent in portions, stirring at 300-500 rpm for 20-30 minutes until the resin is completely dissolved. The temperature should be controlled at ≤40℃ throughout the process to avoid premature temperature-sensitive relaxation of the elastomer and premature dissociation of hydrogen bonds. Medium to high speeds accelerate the dissolution of large resin blocks to prevent resin agglomeration and precipitation. Temperature control at ≤40℃ avoids premature softening of hydrogenated styrene elastomer and premature large-scale association of hydrogen bonds, which would cause abnormal viscosity of the adhesive solution. This ensures that hydrogen bonds are uniformly formed in the subsequent film-forming stage, and significantly improves the storage stability of the adhesive solution.

[0063] Step 3: Dispersion of fillers and antioxidants: Add silane coupling agent grafted with nano-silica and hindered phenolic antioxidants sequentially, and continue stirring for 20-30 minutes to eliminate filler agglomeration and precipitation, ensuring uniform hydrogen bond association; thoroughly stir to disperse agglomerated nano-filler particles to avoid protrusions and particle defects in the adhesive layer; ensure that the antioxidant is uniformly dispersed in the resin system, protecting the resin from oxidation throughout the process; uniform distribution of fillers ensures consistent hydrogen bond association throughout the entire process, and the adhesive layer has no local weak areas.

[0064] Step 4, Mild crosslinking modification: Heat to 50-60℃, adjust the rotation speed to 200-300 r / min and add epoxy-modified silicone resin at a low speed. Stir for 15-20 min to build a mild crosslinking network, retaining the reversible response of resin chain segment movement and hydrogen bonds; heat to 50-60℃ to enhance the reactivity of epoxy groups, and stir at a low speed to control the crosslinking reaction rate, generating only a low-density mild crosslinking network; this achieves high-temperature creep resistance reinforcement without excessive crosslinking that binds resin chains and blocks hydrogen bond dissociation, fully preserving the core function of thermal slip.

[0065] Step 5, Precision Filtration and Purification: A 0.22μm filter membrane is used for vacuum filtration to remove minute impurities and filler agglomerates. The mixture is then sealed, protected from light, and stored at room temperature to obtain a clear and transparent finished bonding adhesive. The 0.22μm precision filtration removes micron-sized impurities and undispersed filler agglomerates, meeting the standards for use in high-cleanliness semiconductor workshops. Light-protected, sealed storage inhibits resin photo-oxidation and solvent evaporation. The finished adhesive solution shows no performance degradation, stratification, or precipitation after 6 months of storage at room temperature.

[0066] This invention also provides a method for temporary wafer bonding using thermally slipped temporary bonding adhesive, comprising the following steps:

[0067] S1. Precision pretreatment of substrate: The wafer and carrier substrate are ultrasonically cleaned with anhydrous ethanol and deionized water, and vacuum dried at 80°C to remove oil, moisture and impurities; thoroughly remove organic oil, particulate impurities and free moisture from the substrate surface, eliminate the interface isolation layer, ensure that the hydrogen bond network of the adhesive layer is tightly bonded to the substrate surface, improve the interface bonding strength, and avoid local debonding and void defects after bonding.

[0068] S2. Spin-coating adhesive layer: The bonding adhesive is spin-coated onto the wafer surface at a spin speed of 3000-5000 r / min and a time of 30-60 s to control the adhesive layer to be uniform and free of bubbles and cavities. The spin speed and time range are precisely controlled to ensure uniform adhesive layer thickness, consistent hydrogen bond density throughout the entire wafer, and uniform bonding strength. The spin-coating process is mature and compatible with semiconductor mass production equipment, and there are no appearance defects such as accumulation, missing coating, or cavities.

[0069] S3. Low-temperature pre-baking to remove solvent: After the wafer and the carrier are precisely bonded, pre-baking is carried out at 80-90℃ for 10-15 minutes to remove residual low-boiling-point solvent and initially establish interfacial adhesion; the residual solvent is slowly evaporated at low temperature to avoid the rapid vaporization of solvent and the formation of bubbles and voids during the subsequent hot pressing stage; hydrogen bonds begin to slowly associate in the low-temperature range to form preliminary interfacial adhesion force, so that the wafer will not slip or misalign after bonding.

[0070] S4. Hot-press permanent temporary bonding: The temperature is increased at a rate of 5℃ / min to 120–150℃, and a pressure of 0.3–0.8 MPa is applied. The temperature and pressure are maintained for 15–20 minutes, forming a stable, slightly cross-linked network in the adhesive layer, achieving temporary fixation of the wafer without voids or slippage. The slow temperature increase of 5℃ / min prevents internal stress caused by thermal shock; the 120–150℃ temperature is below the hydrogen bond dissociation temperature, allowing for full hydrogen bond association and the formation of a stable, slightly cross-linked network in conjunction with the epoxy silicone; uniform pressure eliminates micro-gaps at the interface, ensuring a firm bond across the entire wafer, preventing slippage and debonding throughout the high-temperature processes of thinning, etching, and coating.

[0071] This invention also provides a wafer thermal slip debonding method corresponding to thermal slip temporary bonding adhesive. After the wafer has undergone thinning, etching, and coating processes, the wafer-carrier bonding assembly is placed in a debonding device. The temperature is increased to 180-210°C at a rate of 3°C / min and held for 5-10 minutes. The low heating rate of 3°C / min avoids uneven heating and cooling of the wafer, which can cause warping and breakage. The temperature of 180-210°C precisely matches the hydrogen bond dissociation temperature and the softening range of the hydrogenated elastomer. Holding for 5-10 minutes ensures that the hydrogen bonds in the adhesive layer are fully dissociated and the resin segments are completely softened, resulting in a significant decrease in the modulus of the adhesive layer and a minimum adhesive strength.

[0072] Within this temperature range, hydrogen bonds completely dissociate, the soft segments of the hydrogenated styrene elastomer soften sufficiently, and the modulus of the adhesive layer decreases significantly. By applying slight mechanical thrust or inert gas-assisted purging, the wafer and carrier are thermally separated along the adhesive layer interface. The dissociation of hydrogen bonds eliminates intermolecular interfacial forces, and the softening of the elastomer provides a lubricating sliding matrix. Only slight external force is required to achieve interfacial delamination, resulting in extremely low peel stress and no chipping or scratches on the ultrathin wafer. No covalent bonds break during the peeling process, and the resin is completely desorbed from the substrate without any large molecular fragments embedded on the wafer surface.

[0073] After debonding, the substrate surface has no residual adhesive and can proceed to the next process after simple cleaning. This invention eliminates the need for prolonged immersion in highly toxic, high-boiling-point organic solvents; a short wipe with ordinary alcohols is sufficient to remove trace amounts of loose adhesive. This simplifies the cleaning process, reduces hazardous waste disposal costs, and minimizes the risk of chip device damage from highly corrosive solvents, simultaneously improving environmental friendliness and processing yield.

[0074] This invention breaks through the existing design concept of single resin physical softening and constructs a two-level synergistic system: a physically covalent rigid skeleton: hydrogenated styrene block resin, cyclic olefin copolymer, silane-grafted inorganic filler, and epoxy-modified organosilicon resin form a stable covalent / physical crosslinking skeleton, ensuring high-temperature dimensional stability and solvent resistance of the adhesive layer; a temperature-responsive reversible intermolecular hydrogen bond network: hydrogen-bonded cosolvent hydroxyl groups (donors) + alicyclic acrylic resin ester carbonyl groups (acceptors) form dynamic hydrogen bonds Resin-C=O…HO-R; hydrogen bonds reversibly associate / dissociate with temperature, without covalent bond breakage throughout the process, achieving precise temperature control of adhesive strength; a temperature-sensitive synchronous matching design: the softening temperature of the hydrogenated styrene elastomer chain segments and the hydrogen bond dissociation temperature are uniformly locked at 180-210℃, hydrogen bond dissociation reduces interfacial forces while the resin softens simultaneously, and the dual effects superimposed achieve smooth thermal sliding.

[0075] The main solvent of this invention is a high-boiling-point nonpolar cycloalkanes such as decahydronaphthalene and tetrahydronaphthalene; the co-solvent is a monohydroxy alicyclic alcohol such as α-terpineol and cyclohexanol; the nonpolar main solvent has extremely strong dissolving power for ternary hydrocarbon resins, ensuring that the adhesive solution does not separate or precipitate for a long time; the molecule has no polar groups and does not interfere with hydrogen bond formation; the high boiling point reduces solvent evaporation and bubbles during pre-baking and hot-pressing stages; the hydrogen-bonding co-solvent serves two purposes: first, as a co-solvent, it improves the compatibility between acrylic resin and hydrocarbon resins and reduces system swelling; second, it provides hydroxyl hydrogen bond donors to construct a reversible hydrogen bond network, which is the core small molecule for achieving temperature-controlled bonding; the two are infinitely miscible, and if only a single nonpolar solvent is used, dynamic hydrogen bonds cannot be formed due to the lack of hydrogen bond donors; if only an alcohol solvent is used, hydrogenated elastomers and cycloolefin resins are completely insoluble, and the adhesive solution directly separates and fails; the two are indispensable in the compounding.

[0076] This invention utilizes a fully saturated ABA triblock copolymer with PS hard segments at both ends and an EB / EI soft segment in the middle, containing 14%–50% styrene. It contains no polar groups and does not participate in hydrogen bonding. At room temperature, the PS hard segments undergo microphase separation and physical entanglement, providing basic rigidity and adhesive strength to the adhesive layer. Above 180°C, the hard segments dissociate and the soft segments expand, causing a sharp drop in the adhesive layer modulus, providing a low-modulus matrix required for thermal slip. The temperature-sensitive softening temperature and the hydrogen bond dissociation temperature are precisely synchronized, and their superposition enables peeling. The unhydrogenated SBS contains a large number of unsaturated double bonds, undergoing high-temperature oxidative crosslinking and hardening. The temperature-sensitive region and hydrogen bond dissociation are misaligned, leading to slip failure and a surge in residual adhesive. The cyclic olefin copolymer (TOPAS) is a fully saturated hydrocarbon cyclic polyolefin of ethylene-norbornene, containing no polar groups. It improves the adhesive layer's resistance to NMP, acid, and alkali solvents, and reduces processing swelling. The rigid alicyclic structure enhances the dimensional stability of the adhesive film and helps suppress high-temperature creep. It does not participate in hydrogen bonding and only serves as a solvent-resistant reinforcing phase. Alicyclic acrylic resin: saturated main chain, numerous C=O ester carbonyl groups on side chains, 5% thermal weight loss ≥280℃; the only hydrogen bond acceptor in the system, forming numerous intermolecular hydrogen bonds with the cosolvent hydroxyl groups, significantly improving the cohesive force of the adhesive layer and the bonding strength at room temperature; without this component, the hydrogen bond network cannot be constructed at all, and it will naturally delaminate at room temperature after 3 days; the alicyclic structure also improves heat resistance, and it does not decompose during high-temperature processes.

[0077] The synergistic logic of ternary resins: a single resin cannot simultaneously achieve the three major functions of hydrogen bond formation, temperature-sensitive slip, and solvent resistance; elastomers alone lack hydrogen bond acceptors, resulting in insufficient adhesive strength; acrylic resins alone lack a temperature-sensitive skeleton, making slip impossible at high temperatures; cyclic olefin resins alone lack both adhesive and slip capabilities; the three are combined to form a complementary whole.

[0078] This invention utilizes silane-grafted nano-silica; the Si-OH groups on the surface of native SiO2 undergo hydrolysis and dehydration condensation with a silane coupling agent to generate a ≡Si-O-Si≡ covalent organic grafted layer; the inorganic rigid particles reduce the TTV thickness deviation of the spin-coated adhesive layer; the grafted organic segments exhibit excellent compatibility with the resin, with no interfacial voids; it improves the film's density, high-temperature creep resistance, and solvent swelling resistance; the filler provides only physical reinforcement and does not chemically react with hydroxyl or carbonyl groups, completely avoiding interference with hydrogen bond association / dissociation; after removing the filler, the TTV of the adhesive layer increases from 1.5 μm to 3.8 μm, resulting in a significant decrease in dimensional accuracy.

[0079] The epoxy-modified silicone resin of this invention features a main chain of high-bond-energy Si-O-Si inorganic framework and side chain epoxy groups. It is slowly added during a low-speed stirring stage at 50–60°C, allowing the epoxy groups to form a low-density, slightly cross-linked network at low temperatures. The Si-O-Si framework enhances overall heat resistance. The slight cross-linking further inhibits high-temperature creep and adhesive flow. The extremely low cross-linking density does not restrict resin chain movement or block reversible hydrogen bonding. Removing this component significantly reduces the adhesive's creep resistance and solvent resistance.

[0080] The hindered phenolic antioxidant of the present invention, preferably 1076, captures free radicals of resin oxidation at high temperatures, inhibits thermal degradation and yellowing of hydrogenated elastomers and acrylic resins; the molecule has no strongly polar hydroxyl / carbonyl groups, does not consume hydrogen bond donors and acceptors, and does not destroy the hydrogen bond network; without antioxidants, the resin oxidizes and ages after multiple thermal cycles, the bonding strength continues to decline, and the long-term process stability is insufficient.

[0081] The key process features of this invention are step-by-step temperature control, rotation speed control, and material feeding sequence. Each process parameter corresponds to the molecular structure control target: 25-35℃ premixed composite solvent: low temperature avoids the volatilization of alcohol co-solvents and ensures uniform dispersion of hydrogen bond donors; ≤40℃ dissolution of ternary resin: prevents premature softening of hydrogenated elastomers and uneven premature association of hydrogen bonds, avoiding abnormal local viscosity of the adhesive; 300-500 r / min high rotation speed accelerates resin dissolution; room temperature dispersion of fillers and antioxidants: high rotation speed breaks up filler agglomerates, ensuring uniform distribution of inorganic particles and reducing TTV; 50-60℃ low-speed addition of epoxy silicone: low rotation speed avoids excessive crosslinking, forming only mild low-density crosslinking, preserving hydrogen bond and chain segment mobility; 0.22μm precision filtration: removes micron-sized impurities and filler agglomerates, adapting to the high cleanliness requirements of semiconductor processes.

[0082] In the bonding process of this invention, the process proceeds in four progressive steps: pretreatment → spin coating → low-temperature pre-baking → gradient heating hot pressing, eliminating defects layer by layer: precise cleaning and drying of the substrate: thoroughly removing interface contaminants and ensuring adhesion between the hydrogen bonding system and the substrate interface; precise thickness control of spin coating: ensuring uniform adhesive layer with consistent hydrogen bond density throughout the entire area, and no local weak areas in the bond; pre-baking at 80-90℃: slowly removing residual low-boiling-point solvents to prevent solvent evaporation and the generation of air bubbles and voids during the hot pressing stage; hot pressing and heat preservation at 120-150℃: this temperature is below the hydrogen bond dissociation temperature, allowing hydrogen bonds to fully associate and a slightly cross-linked network to form, achieving permanent and temporary fixation, with no slippage or debonding throughout the entire process.

[0083] In the thermal slip debonding process of this invention, the temperature is slowly increased to 180-210°C at a rate of 3°C / min and held for 5-10min. The temperature range is matched so that hydrogen bonds dissociate extensively above 180°C, and intermolecular forces disappear. At the same time, the soft segments of the hydrogenated elastomer soften completely, and the modulus of the adhesive layer drops sharply. The slip separation mechanism is based on the superposition of double softening and dissociation, which allows separation along the adhesive layer interface with only slight external force. There is no tearing stress, and the ultra-thin wafer is free from breakage. Residual adhesive control is achieved because the hydrogen bonds dissociate reversibly without the breakage of covalent bonds. The resin is desorbed from the substrate interface as a whole, leaving no large molecular fragments, thus achieving a Class A residue-free effect.

[0084] This invention relies on the dynamic hydrogen bonding of hydroxyl-carbonyl groups to combine the temperature-sensitive properties of the resin, taking into account both room temperature bonding strength and high temperature non-destructive peeling performance. It is combined with functional fillers and additives to improve the dimensional stability, solvent resistance and thermal stability of the adhesive film. The adhesive layer has small thickness deviation and leaves no adhesive residue after debonding. It can be adapted to the entire precision process of semiconductor ultrathin wafer thinning, etching and coating.

[0085] The raw materials used in this invention are as follows: the nonpolar main solvent is selected from decahydronaphthalene, tetrahydronaphthalene, and p-menthane; the hydrogen-bonding cosolvent is selected from α-terpineol, β-terpineol, cyclohexanol, and cyclopentanol; the ternary main resin is selected from hydrogenated styrene-ethylene-butene block copolymer (SEBS), cyclic olefin copolymer (TOPAS5013L-10, TOPAS6013F-17), and alicyclic acrylic resin (DianalBR-106, DianalBR-113); the silane covalently grafted modified filler is selected from silane coupling agent grafted nano-silica, siloxane grafted nano-alumina, and silane grafted talc; the epoxy modified organosilicon resin is selected from semiconductor-specific temperature-resistant type; the hindered phenolic antioxidants are selected from antioxidant 1135, antioxidant 1076, and antioxidant 405. In this system, the hydroxyl group of the hydrogen-bonded cosolvent acts as a hydrogen bond donor, and the ester carbonyl group of the alicyclic acrylic resin acts as a hydrogen bond acceptor, forming a stable hydroxyl-carbonyl thermally reversible hydrogen bond. At the same time, SEBS has a specific temperature-sensitive range, and its chain segment softening temperature is consistent with the hydrogen bond dissociation temperature, achieving synergistic performance.

[0086] Example 1: 64 parts by weight of nonpolar main solvent (decahydronaphthalene), 15 parts by weight of hydrogen-bonded co-solvent (α-terpineol), 42 parts by weight of ternary main resin (SEBS+TOPAS5013L-10+DianalBR-106), 3.2 parts by weight of silane coupling agent-grafted nano-silica, 0.5 parts by weight of epoxy-modified organosilicon resin, and 0.3 parts by weight of antioxidant 1076. This example demonstrates modification through the combination of a nonpolar main solvent, hydrogen-bonded co-solvent, ternary resin, silane-modified filler, epoxy-modified organosilicon resin, and hindered phenolic antioxidant. The hydroxyl groups of α-terpineol combine with the ester carbonyl groups of the alicyclic acrylic resin to form thermally reversible hydrogen bonds. Furthermore, the softening temperature of the SEBS chain segments is consistent with the hydrogen bond dissociation temperature, resulting in a glue solution with high stability, excellent dimensional accuracy, resistance to photolithography solvents, high-temperature stability, smooth thermal slippage, and no residue.

[0087] Preparation steps: First, a nonpolar main solvent and a hydrogen-bonding co-solvent are mixed and stirred at a constant temperature of 25–35°C for 10–15 min to obtain a homogeneous and transparent composite hydrogen-bonding solvent. Then, a ternary main resin is added, and the stirring speed is controlled at 300–500 r / min for 20–30 min until completely dissolved. The temperature is controlled not to exceed 40°C throughout the process. Silane covalently grafted nano-silica and antioxidant are added sequentially, and stirred for 20–30 min. The temperature is then raised to 50–60°C, and the stirring speed is adjusted to 200–300 r / min. Epoxy-modified organosilicon resin is added and stirred at low speed for 15–20 min. Finally, the mixture is filtered under reduced pressure using a 0.22 μm precision filter membrane, and stored in a sealed, light-protected container at room temperature to obtain the finished thermally slipping temporary bonding adhesive.

[0088] Example 2: 62 parts by weight of nonpolar main solvent (decahydronaphthalene), 17 parts by weight of hydrogen-bonded co-solvent (α-terpineol), 43 parts by weight of ternary main resin (SEBS+TOPAS6013F-17+DianalBR-113), 3.5 parts by weight of siloxane-grafted nano-alumina, 0.6 parts by weight of epoxy-modified silicone resin, and 0.4 parts by weight of antioxidant 1076. The preparation process is completely consistent with Example 1. In this example, through the combined modification of a high proportion of hydrogen-bonded co-solvent, a high solvent-resistant cyclic olefin copolymer, alicyclic acrylic resin, and siloxane-grafted nano-alumina, the number of hydrogen bonds formed between α-terpineol and alicyclic acrylic resin is further increased. The temperature-sensitive properties of SEBS remain synchronized with the changes in hydrogen bonds, resulting in further improved solvent resistance and stronger high-temperature creep resistance of the adhesive layer.

[0089] Example 3: 68 parts by weight of nonpolar main solvent (tetrahydronaphthalene + cyclohexane), 12 parts by weight of hydrogen-bonding co-solvent (cyclopentanol), 41 parts by weight of ternary main resin (SEPS + TOPAS5013L-10 + DianalBR-106), 3.0 parts by weight of silane-grafted talc, 0.4 parts by weight of epoxy-modified silicone resin, and 0.2 parts by weight of antioxidant 405. The preparation process is completely consistent with Example 1. In this example, by increasing the amount of nonpolar main solvent and combining it with the modification of cyclopentanol and silane-grafted talc, the cyclopentanol hydroxyl group and the carbonyl group of the alicyclic acrylic resin ester normally construct thermally reversible hydrogen bonds. The temperature-sensitive range of SEPS matches the hydrogen bond dissociation temperature, resulting in a low viscosity adhesive with excellent spin-coating and spreading properties, suitable for low-temperature debonding conditions.

[0090] Comparative Example 1: In Example 1, α-terpineol was replaced with anhydrous ethanol in equal amounts. All other components, weight parts, and preparation processes remained the same as in Example 1. This was used to verify the necessity of selecting a hydrogen-bonding co-solvent. This comparative example modified the system by replacing the weakly polar hydrogen-bonding co-solvent with strongly polar anhydrous ethanol. Anhydrous ethanol cannot form stable hydrogen bonds with alicyclic acrylic resins, and the two have extremely poor miscibility, leading to problems such as resin separation and precipitation, ultimately causing the system to fail.

[0091] Comparative Example 2: In Example 1, SEBS was replaced in equal amounts with unhydrogenated styrene-butadiene block copolymer (SBS). All other components, weight parts, and preparation processes remained consistent with Example 1. This comparative example was used to verify the effect of the hydrogenated elastomer. By replacing the fully hydrogenated elastomer with the unhydrogenated block resin, the resin lost its thermosensitive properties matching hydrogen bonds. At high temperatures, it could not soften synchronously with the dissociation of hydrogen bonds, ultimately resulting in adverse effects such as high-temperature crosslinking hardening, loss of thermal slip function, and increased residual resin.

[0092] Comparative Example 3: The epoxy-modified silicone resin in Example 1 was removed, while the remaining components, weight parts, and preparation process remained consistent with Example 1. This example was used to verify the reinforcing effect of the temperature-modified resin. In this comparative example, by removing the epoxy-modified silicone resin component, the hydrogen bonding state and temperature-sensitive characteristics of SEBS within the system remained unchanged. However, the adhesive layer lacked a reinforcing structure, resulting in increased adhesive layer thickness deviation and decreased solvent resistance and creep resistance.

[0093] Comparative Example 4: Antioxidant 1076 was removed from Example 1, while the remaining components, weight parts, and preparation process remained consistent with Example 1. This example was used to verify the effect of antioxidants on thermal cycling stability. This comparative example, through modification by removing hindered phenolic antioxidants, maintained the hydrogen bonding system and SEBS temperature-sensitive properties normally, but the long-term thermal stability of the resin decreased, resulting in the material yellowing and exhibiting reduced adhesive performance after multiple thermal cycles.

[0094] Comparative Example 5: The alicyclic acrylic resin from Example 1 was removed, and only SEBS and TOPAS5013L-10 were retained as the ternary main resin, with a total weight of 42 parts. All other components, weight parts, and preparation processes remained consistent with Example 1. This was used to verify the role of the hydrogen bond acceptor component. This comparative example, modified by removing the alicyclic acrylic resin, lacked the ester carbonyl hydrogen bond acceptor, making it unable to form hydroxyl-carbonyl hydrogen bonds with hydrogen-bonding cosolvents. Although SEBS still retained its original temperature-sensitive properties, its adhesive strength at room temperature decreased significantly, and the samples easily detached naturally.

[0095] Comparative Example 6: The silane covalently grafted nano-silica filler in Example 1 was removed, while the remaining components, weight parts, and preparation process remained consistent with Example 1. In this comparative example, by removing the silane-grafted inorganic filler, the reversible hydrogen bonds of hydroxyl-carbonyl groups and the temperature-sensitive softening properties of SEBS were fully retained. No component disrupted hydrogen bond donor-acceptor pairing, but the inorganic rigid reinforcing framework was lacking. The adhesive layer lacked nanoparticle filling constraint, allowing resin molecular chains to flow freely at high temperatures, significantly reducing the film density. After spin coating, the thickness deviation (TTV) of the adhesive layer increased significantly, allowing photolithography solutions such as NMP to easily penetrate the adhesive layer and cause swelling. High-temperature processes resulted in severe creep of the adhesive layer, making it prone to misalignment during wafer processing, increasing thermal slip separation resistance, and comprehensively deteriorating overall dimensional stability and chemical corrosion resistance.

[0096] Table 1. Raw material ratios (parts by weight) for each group of samples. Example 1 64 (Decahydronaphthalene) 15 (α-terpineol) 42 SEBS 50 servings + TOPAS5013L-10 49 servings + DianalBR-106 1 serving 3.2 (Nano Silica) 0.5 0.3(1076) High solvent resistance standards: lower limit for elastomers 50 parts, upper limit for cycloolefins 49 parts, lower limit for acrylic acid 1 part Example 2 62 (Decahydronaphthalene) 17 (α-terpineol) 43 SEBS 98 servings + TOPAS6013F-17 1 serving + DianalBR-113 1 serving 3.5 (Nano Alumina) 0.6 0.4(1076) High-slip formulation: elastomer upper limit 98 parts, cycloolefin lower limit 1 part, acrylic acid lower limit 1 part Example 3 68 (tetrahydronaphthalene + cyclohexane) 12 (Cyclopentanol) 41 SEPS 50 servings + TOPAS5013L-10 1 serving + DianalBR-106 49 servings 3.0 (talcum powder) 0.4 0.2(405) High-adhesion formulation: elastomer lower limit 50 parts, cycloolefin lower limit 1 part, acrylic acid upper limit 49 parts Comparative Example 1 64 (Decahydronaphthalene) 15 (anhydrous ethanol) 42 SEBS 50 servings + TOPAS5013L-10 49 servings + DianalBR-106 1 serving 3.2 (Nano Silica) 0.5 0.3(1076) Replacement cosolvent Comparative Example 2 64 (Decahydronaphthalene) 15 (α-terpineol) 42 (replaces SBS) SBS 50 servings + TOPAS5013L-10 4 servings + DianalBR-106 1 serving 3.2 (Nano Silica) 0.5 0.3(1076) Unhydrogenated elastomers Comparative Example 3 64 (Decahydronaphthalene) 15 (α-terpineol) 42 SEBS 50 servings + TOPAS5013L-10 49 servings + DianalBR-10 61 servings 3.2 (Nano Silica) 0 0.3(1076) Remove silicone resin Comparative Example 4 64 (Decahydronaphthalene) 15 (α-terpineol) 42 SEBS 50 servings + TOPAS5013L-10 49 servings + DianalBR-106 1 serving 3.2 (Nano Silica) 0.5 0 Remove antioxidants Comparative Example 5 64 (Decahydronaphthalene) 15 (α-terpineol) 42 (Remove acrylic resin) SEBS 99 parts + TOPAS5013L-10 1 part, acrylic resin 0 parts 3.2 (Nano Silica) 0.5 0.3(1076) Eliminate acrylic resin Comparative Example 6 64 (Decahydronaphthalene) 15 (α-terpineol) 42 SEBS 50 servings + TOPAS5013L-10 49 servings + DianalBR-106 1 serving 0 (Silane-free grafted inorganic filler) 0.5 0.3(1076) Elimination of silane-modified fillers

[0097] Test conditions: Ambient temperature 25℃. Samples were prepared according to the standard spin coating, pre-baking, hot pressing at 130℃, and hot slip debonding process of this invention. Criteria for judging indicators: Adhesive appearance: Visual inspection of adhesive appearance; TTV after bonding: TTV test was performed by scanning the bonded wafers with a white light interferometer. Five wafers were tested for each sample, and the average value was taken; NMP corrosion resistance: Immersion in NMP solvent at 80℃ for 30 minutes, and observation was made for whether there was any peeling, swelling, or dissolution.

[0098] 220℃ Thermal Stability Rating: Ⅰ=No yellowing or foaming after 30 min of heat treatment; Ⅱ=Slight yellowing; Ⅲ=Hardening, foaming failure; Thermal Sliding Rating: 1=Smooth sliding without jamming; 2=High sliding resistance, local adhesion; 3=Cannot be completely peeled off; Residual Adhesive Rating: A=No visible residual adhesive under an optical microscope; B=Trace amount of dotted residual adhesive; C=Large area of ​​resin residue; Room Temperature Bonding Stability: Observe whether the wafer and the carrier substrate slip or detach after 7 days of storage at room temperature.

[0099] FTIR hydrogen bond peak relative area: FTIR Fourier transform infrared spectroscopy was used to test two sets of samples: an untreated film at room temperature and a film treated at 200℃ for 10 min. The infrared spectral scanning band covered the 3000–3600 cm⁻¹ characteristic region of associated hydroxyl groups and the 1700–1750 cm⁻¹ characteristic region of ester carbonyl groups. The integrated area of ​​the carbonyl peak of the sample at room temperature in Example 1 was used as the quantitative benchmark, and the relative area of ​​the hydrogen bond characteristic peaks of all samples was calculated by normalization. The integrated area of ​​the characteristic peaks is positively correlated with the number of hydrogen bonds in the system, which can quantitatively evaluate the hydrogen bond construction effect and high-temperature dissociation behavior of different formulations.

[0100] SEM cross-sectional microstructure testing: The cross-section of the adhesive film was prepared using a liquid nitrogen cryogenic brittle fracture process to avoid tensile deformation and artificial cracks caused by room temperature mechanical fracture. A 5-15 nm conductive gold layer was sputtered onto the cross-section surface to eliminate charged white spots. Scanning electron microscopy was used to observe the filler aggregation, the compatibility of the resin and silane-modified filler interface, and the internal pore defects of the adhesive layer. At least five images from different fields of view were selected, and the cross-section pore ratio was statistically analyzed using an image binarization algorithm. The porosity value directly reflects the density of the adhesive film; the higher the porosity, the more channels for drug penetration and the worse the resistance to solvent swelling. Liquid nitrogen brittle fracture combined with gold sputtering is the industry standard sample preparation method for hydrocarbon flexible polymer films, which can truly reflect the original microstructure of the adhesive layer.

[0101] Table 2 Comprehensive Performance Test Results Example 1 Clarity and transparency 1.5 No shedding, no swelling, no dissolution Ⅰ 1 A 100 0.28 No debonding Example 2 Clarity and transparency 1.7 No shedding, no swelling, no dissolution Ⅰ 1 A 101 0.31 No debonding Example 3 Clarity and transparency 1.9 No shedding, no swelling, no dissolution Ⅰ 1 A 149 0.36 No debonding Comparative Example 1 Turbidity and layering - The adhesive layer separated, making sample preparation and testing impossible. - - - 12 Numerous holes Layered precipitation Comparative Example 2 Clarity and transparency 2.0 No shedding, no swelling, no dissolution Ⅲ 3 C 96 1.24 Short-term normal Comparative Example 3 Clarity and transparency 4.0 No shedding, no swelling, no dissolution Ⅰ 1 A 99 0.86 No debonding Comparative Example 4 Clarity and transparency 1.6 No shedding, no swelling, no dissolution II (After thermal cycling) 1 A 98 0.30 Later localized detachment Comparative Example 5 Clarity and transparency 1.9 No shedding, no swelling, no dissolution Ⅰ 2 A 10 0.32 3D debonding Comparative Example 6 Clarity and transparency 4.2 Significant swelling Ⅰ 2 A 99 1.11 No debonding, extremely poor thickness uniformity

[0102] Note: The light transmittance of the adhesive is ≥90% to indicate uniformity and stability; the acceptable threshold for TTV is ≤2.0μm; the acceptable threshold for NMP swelling rate is ≤3.0%; high temperature thermal stability level: I-no yellowing or foaming, II-slight yellowing, III-significant hardening and failure;

[0103] Heat slippage rating: 1-Smooth slippage, 2-Slippage jamming, 3-Cannot be peeled off; Residual adhesive rating: A-No visible adhesive residue, B-Trace amount of adhesive residue, C-Large amount of adhesive residue.

[0104] As shown in Table 2, the adhesive solutions in Examples 1-3 of this invention are all clear and transparent, with no stratification or precipitation during long-term storage; the TTV of the adhesive layer is controlled within 1.9 μm, and there is no peeling, swelling, or dissolution in terms of NMP corrosion resistance, and no deterioration at 220℃. The synergistic effect of the hydrogen-bonded co-solvent and the hydroxyl-carbonyl hydrogen bonds formed by the alicyclic acrylic resin, along with the temperature-sensitive softening properties of SEBS, results in smooth thermal sliding at 200℃, no visible adhesive residue after debonding, and strong adhesion after 7 days at room temperature. All indicators meet the requirements of precision processes for ultra-thin semiconductor wafers.

[0105] Table 3. Rheological and microscopic characterization results FTIR The sample at room temperature showed a characteristic peak for hydroxyl groups at 3200–3400 cm⁻¹ and a characteristic peak for ester carbonyl groups at 1735 cm⁻¹; after testing at 200℃, the intensity of the characteristic peaks for hydroxyl and carbonyl groups decreased significantly. This demonstrates that at room temperature, the hydroxyl group of α-terpineol forms a -OH…O=C- hydrogen bond with the carbonyl group of alicyclic acrylic resin ester, and the hydrogen bond dissociates upon heating at high temperatures; simultaneously, this temperature range coincides with the softening temperature of the SEBS chain segment, achieving synergistic temperature control. FTIR Compared with Comparative Example 5, the peak intensities of the carbonyl characteristic peaks in Examples 1, 2, and 3 are significantly higher. Alicyclic acrylic resins act as hydrogen bond core acceptors; their absence prevents the formation of effective hydrogen bonds, resulting in a significant decrease in adhesive strength at room temperature. SEM Example 1: The adhesive layer has a dense cross-section, with a blurred interface between the inorganic filler and the resin, and no obvious voids. Silane-modified fillers exhibit excellent compatibility with resins, high interfacial bonding strength, and hydrogen bond networks further enhance the overall system integrity. SEM Comparative Example 2 showed numerous cracks in the cross-section of the adhesive layer, indicating embrittlement of the resin matrix. The temperature sensitivity of unhydrogenated SBS does not match its hydrogen bond dissociation temperature, making it unable to soften synchronously at high temperatures and prone to cross-linking degradation. SEM Comparative Example 3: Micropores exist inside the adhesive layer. The lack of epoxy-modified silicone resin reduced the film density, but the synergistic effect of hydrogen bonding and resin was not affected. SEM Comparative Example 6: The adhesive layer contains numerous interconnected micropores, and the resin matrix lacks rigid particle dispersion support. Without silane-grafted inorganic fillers, the lack of a dense organic-inorganic composite framework results in a porous film that is easily penetrated and swollen by solvents, leading to a significant deterioration in thickness uniformity.

[0106] Comparative Example 1: When weakly polar terpineol was replaced with strongly polar anhydrous ethanol, ethanol was difficult to use as a stable hydrogen bond donor to bind with alicyclic acrylic resin. At the same time, the two types of solvents had large differences in polarity and poor miscibility, resulting in a large amount of resin agglomeration and precipitation. The transmittance of the adhesive was only 45%, and the system was completely ineffective. This proves that the hydrogen-bonded weakly polar alcohol cosolvent specified in this invention is an essential component.

[0107] Comparative Example 2: Using unhydrogenated SBS instead of hydrogenated SEBS, the softening temperature of SBS segments and the hydrogen bond dissociation temperature could not be matched, and the molecules contained a large number of unsaturated double bonds. Oxidative crosslinking occurred at high temperature, the resin hardened, and thermal sliding could not be achieved after hydrogen bond dissociation. A large amount of residual glue was generated after peeling, which verified that fully hydrogenated styrene block resin is the key to ensuring high temperature temperature-sensitive properties.

[0108] Comparative Example 3: Without epoxy-modified silicone resin, the film lacks a slightly cross-linked reinforcing network, but the hydrogen bonding state and SEBS temperature-sensitive properties remain normal, only showing a decrease in high-temperature creep resistance and solvent resistance. The Si-O-Si inorganic framework and slightly cross-linked network of epoxy-modified silicone are key reinforcing structures for inhibiting solvent swelling. Even with intact hydrogen bonds, the film's density decreases significantly and the swelling rate increases markedly after the epoxy silicone is removed. However, because the hydrogen bond network still exists, the swelling performance is still better than that of Comparative Example 5, which completely lacks hydrogen bond acceptors.

[0109] Comparative Example 4: Without the addition of hindered phenolic antioxidants, the resin gradually oxidizes under repeated thermal cycling. Although the hydrogen bonding and SEBS temperature response characteristics are normal in the short term, the overall aging of the resin leads to a decline in adhesive performance, making it unsuitable for long-term high-temperature semiconductor processes.

[0110] Comparative Example 5: After removing the alicyclic acrylic resin, the system lacks ester carbonyl hydrogen bond acceptors and cannot form hydroxy-carbonyl hydrogen bonds with hydrogen-bonding cosolvents. Even if SEBS retains its original temperature-sensitive properties, the bonding strength at room temperature cannot meet the requirements. The sample slipped and debonded after 3 days, confirming that the resin is the core component for constructing thermally reversible hydrogen bonds.

[0111] Comparative Example 6: Without silane coupling agent grafted with nano-silica, the system lacks a rigid inorganic reinforcing framework, which cannot constrain the high-temperature flow of resin molecular chains or fill the pores of the adhesive layer. Although the reversible hydrogen bond system and the temperature-sensitive slip characteristics of SEBS are not affected, the uniformity of adhesive layer thickness, density, solvent resistance and creep resistance are comprehensively deteriorated, the thermal slip resistance increases and the wafer is prone to shifting. This confirms that silane-grafted inorganic fillers are necessary reinforcing components to ensure low TTV, high resistance to chemical solutions and high-temperature dimensional stability.

[0112] In summary, the following results were observed: Lack of hydrogen-bonding cosolvent (Comparative Example 1): No hydrogen bond donors, resulting in adhesive layering and failure at room temperature; Lack of alicyclic acrylic resin (Comparative Example 5): No hydrogen bond acceptors, inability to construct reversible hydrogen bonds, and insufficient adhesive strength at room temperature; Replacing the hydrogenated elastomer with SBS (Comparative Example 2): The temperature-sensitive range and hydrogen bond dissociation were asynchronous, leading to high-temperature crosslinking and hardening, slippage failure, and significant residue; Removal of epoxy-modified silicone resin (Comparative Example 3): Significantly reduced creep resistance and dimensional accuracy of the adhesive layer, with excessive TTV; Removal of hindered phenolic antioxidants (Comparative Example 4): Resin aging due to long-term thermal cycling, resulting in decreased adhesive performance; Removal of silane-grafted inorganic fillers (Comparative Example 6): Poor adhesive layer density, inadequate solvent resistance, thickness uniformity, and high-temperature creep resistance, leading to increased slippage resistance. This invention utilizes a scientifically formulated combination of components. The thermally reversible hydrogen bonds formed by the hydrogen-bonded cosolvent hydroxyl group and the carbonyl group of the alicyclic acrylic resin ester, combined with the SEBS hydrogenated elastomer that synchronizes with the temperature-sensitive range, form a core temperature control system. The synergistic effect of binary compound solvents, silicon-based modified fillers, epoxy silicone resin and hindered phenolic antioxidants results in products with excellent dimensional accuracy, high temperature resistance, solvent resistance and cleanliness.

Claims

1. A thermally slipped temporary bonding adhesive based on hydrogen bond regulation, characterized in that, The product comprises, by weight, the following components: 56-68 parts of nonpolar main solvent; 12-17 parts of hydrogen-bonded co-solvent; 40-46 parts of ternary host resin; 2.8-4.2 parts of silane-grafted inorganic filler; 0.4-0.7 parts of epoxy-modified silicone resin; and 0.2-0.5 parts of hindered phenolic antioxidant. The nonpolar main solvent and the hydrogen-bonded co-solvent are miscible to form a composite solvent system, and the composite solvent forms a thermally reversible intermolecular hydrogen bond system with the ternary host resin. The ternary host resin is composed of hydrogenated styrene. The product is a compound of olefinic elastomer, cyclic olefin copolymer, and alicyclic acrylic resin; a hydrogen-bonding cosolvent carries hydroxyl groups as hydrogen bond donors, and the alicyclic acrylic resin side chain carbonyl groups in the ternary main resin act as hydrogen bond acceptors; the silane-grafted inorganic filler and epoxy-modified organosilicon resin construct a low-density physical / mildly cross-linked reinforcing network; the hydrogen-bonding cosolvent is a weakly polar alicyclic alcohol containing a single hydroxyl group and a normal pressure boiling point of 100-220℃, selected from one or more of α-terpineol, β-terpineol, cyclohexanol, and cyclopentanol.

2. The hydrogen-bonded thermally sliding temporary bonding adhesive according to claim 1, characterized in that: The nonpolar primary solvent is a cycloalkanes / fused-ring hydrocarbons containing carbon and hydrogen elements, nonpolar functional groups, and with a boiling point ≥150℃ at normal pressure, selected from any one or more of decahydronaphthalene, tetrahydronaphthalene, and p-menthane.

3. The hydrogen-bonded thermally sliding temporary bonding adhesive according to claim 1, characterized in that, Based on 100 parts by weight of the total ternary resin: 50-98 parts of hydrogenated styrene elastomer; 1-49 parts of cyclic olefin copolymer; 1-49 parts of alicyclic acrylic resin; the hydrogenated styrene elastomer is a fully saturated ABA-type hydrogenated block copolymer, selected from one or more of hydrogenated polystyrene-poly(ethylene / propylene) block copolymer, hydrogenated styrene-ethylene-butene-styrene block copolymer, and hydrogenated styrene-isoprene-styrene triblock copolymer; the cyclic olefin copolymer is an ethylene-norbornene fully saturated polyolefin, used to improve the solvent resistance and rigidity of the adhesive layer; the alicyclic acrylic resin is a thermoplastic random copolymer with a saturated main chain and ester carbonyl groups on the side chains, forming reversible -OH…O=C- intermolecular hydrogen bonds with the hydroxyl groups of hydrogen-bonded cosolvents.

4. The hydrogen-bonded thermally sliding temporary bonding adhesive according to claim 1, characterized in that: The silane-grafted inorganic filler is selected from one or more of the following: silane coupling agent grafted nano-silica, siloxane grafted nano-alumina, silane grafted talc, and silane grafted montmorillonite.

5. The hydrogen-bonded thermally sliding temporary bonding adhesive according to claim 1, characterized in that: The epoxy-modified silicone resin has a main chain of Si-O-Si inorganic covalent bonds and side links with epoxy active groups.

6. The hydrogen-bonded thermally sliding temporary bonding adhesive according to claim 1, characterized in that: The hindered phenolic antioxidant is selected from one or more of antioxidant 1135, antioxidant 1076, and antioxidant 405.

7. The hydrogen-bonded thermally slipped temporary bonding adhesive according to claim 1, characterized in that, The product comprises the following components by weight: 62-68 parts of tetrahydronaphthalene as the nonpolar main solvent; 12-17 parts of α-terpineol as the hydrogen-bonding co-solvent; 41-42 parts of a ternary main resin, which is a compound of hydrogenated styrene-ethylene-butene block copolymer, cyclic olefin copolymer, and alicyclic acrylic resin; 3.0-3.2 parts of silane coupling agent grafted with nano-silica; 0.4-0.5 parts of epoxy-modified organosilicon resin; and 0.2-0.3 parts of 1076 as the antioxidant.

8. A method for preparing a hydrogen-bonded, hydrogen-controlled, thermally slipped temporary bonded adhesive as described in any one of claims 1 to 7, characterized in that, It includes the following steps: Step 1: Mix the nonpolar main solvent with the hydrogen-bonded co-solvent, and stir at a constant temperature of 25-35℃ for 10-15 minutes to obtain a homogeneous and transparent composite solvent. Step 2: Add the ternary main resin to the composite solvent in portions, stir at 300-500 r / min for 20-30 min until the resin is completely dissolved, and keep the temperature ≤40℃ throughout the process; Step 3: Add silane coupling agent grafted nano-silica and hindered phenolic antioxidant in sequence, and continue stirring for 20-30 minutes; Step 4: Heat to 50-60℃, adjust the rotation speed to 200-300r / min and add epoxy-modified silicone resin at low speed, stir for 15-20min to build a mild cross-linked network; Step 5: Use a 0.22μm filter membrane to filter under reduced pressure to remove tiny impurities and filler agglomerates. Seal and store at room temperature in a dark place to obtain a clear and transparent finished bonding adhesive.

9. A wafer temporary bonding method using a thermally slipped temporary bonding adhesive as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. The wafer and carrier substrate are ultrasonically cleaned with anhydrous ethanol and deionized water, and then vacuum dried at 80°C to remove oil, moisture and impurities. S2. Spin-coat the bonding adhesive onto the wafer surface at a spin speed of 3000-5000 r / min and a time of 30-60 s, ensuring the adhesive layer is uniform and free of bubbles and pores. S3. After the wafer and the carrier are precisely bonded, pre-bake at 80-90℃ for 10-15 minutes to remove residual low-boiling-point solvents and initially establish interfacial adhesion. S4. Increase the temperature at a rate of 5℃ / min to 120~150℃, apply a pressure of 0.3~0.8MPa, and maintain the temperature and pressure for 15~20min. The adhesive layer forms a stable, slightly cross-linked network, completing the temporary fixation of the wafer without voids or slippage.

10. A wafer thermal slip debonding method corresponding to the thermal slip temporary bonding adhesive according to any one of claims 1 to 7, characterized in that: After the wafer has undergone thinning, etching, and coating processes, the wafer-carrier bonding assembly is placed in a debonding device, and the temperature is increased to 180-210°C at a rate of 3°C / min, and held for 5-10 minutes. In this temperature range, the hydrogen bonds are completely dissociated, the soft segments of the hydrogenated styrene elastomer are fully softened, and the modulus of the adhesive layer decreases. Mechanical thrust or inert gas-assisted purging is applied to thermally slide the wafer and carrier apart along the adhesive layer interface.

Citation Information

Patent Citations

  • Corrosion-resistant and heat-resistant temporary bonding glue, preparation method and bonding and de-bonding method

    CN120737764A

  • Temporary bonding glue for wafer thinning in high-temperature-resistant process

    CN121160256A